Dealing with aflatoxin B(1) dihydrodiol acute effects: Impact of aflatoxin B(1)-aldehyde reductase enzyme activity in poultry species tolerant to AFB(1) toxic effects - Murcia, Hansen (PLoS One, 2020)
Aflatoxin B(1) aldehyde reductase (AFAR) enzyme activity has been associated to a higher resistance to the aflatoxin B(1) (AFB(1)) toxicity in ethoxyquin-fed rats. However, no studies about AFAR activity and its relationship with tolerance to AFB(1) have been conducted in poultry. To determine the role of AFAR in poultry tolerance, the hepatic in vitro enzymatic activity of AFAR was investigated in liver cytosol from four commercial poultry species (chicken, quail, turkey and duck). Specifically, the kinetic parameters V(max), K(m) and intrinsic clearance (CL(int)) were determined for AFB(1) dialdehyde reductase (AFB(1)-monoalcohol production) and AFB(1) monoalcohol reductase (AFB(1)-dialcohol production). In all cases, AFB(1) monoalcohol reductase activity saturated at the highest aflatoxin B(1) dialdehyde concentration tested (66.4 μM), whereas AFB(1) dialdehyde reductase did not. Both activities were highly and significantly correlated and therefore are most likely catalyzed by the same AFAR enzyme. However, it appears that production of the AFB(1) monoalcohol is favored over the AFB(1) dialcohol. The production of alcohols from aflatoxin dialdehyde showed the highest enzymatic efficiency (highest CL(int) value) in chickens, a species resistant to AFB(1); however, it was also high in the turkey, a species with intermediate sensitivity; further, CL(int) values were lowest in another tolerant species (quail) and in the most sensitive poultry species (the duck). These results suggest that AFAR activity is related to resistance to the acute toxic effects of AFB(1) only in chickens and ducks. Genetic selection of ducks for high AFAR activity could be a means to control aflatoxin sensitivity in this poultry species.